Electron-transfer-mediated decay and interatomic coulombic decay from the triply ionized states in argon dimers - Sakai, Kenji; Stoychev, S.; Ouchi, T.; Higuchi, I.; Schöffler, M.; Mazza, T.; Fukuzawa, H.; Nagaya, K.; Yao, M.; Tamenori, Y.; Kuleff, Alexander I.; Saito, N.; et al. (Physical review letters, 2011)
We report the first observation of electron-transfer-mediated decay (ETMD) and interatomic Coulombic decay (ICD) from the triply charged states with an inner-valence vacancy, using the Ar dimer as an example. These ETMD and ICD processes, which lead to fragmentation of Ar3+−Ar into Ar2+−Ar2+ and Ar3+−Ar+, respectively, are unambiguously identified by electron-ion-ion coincidence spectroscopy in which the kinetic energy of the ETMD or ICD electron and the kinetic energy release between the two fragment ions are measured in coincidence.